Consider an -degree polynomial that satisfies the following condition:
Find the value of when
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let Q ( x ) = ( x + 1 ) P ( x ) − x
( x + 1 ) P ( x ) − x = c x ( x − 1 ) ( x − 2 ) ⋅ ⋅ ⋅ ( x − n )
Put x = − 1 and get 1 = c ( − 1 ) n + 1 ( n + 1 ) !
P ( x ) = x + 1 ( − 1 ) n + 1 x ( x − 1 ) ⋅ ⋅ ⋅ ( x − n ) / ( n + 1 ) ! + x
P ( n + 1 ) = { 1 for odd n , n + 2 n for even n